Improving the onboarding program of an IT consulting development team - Revilla, Maribeth (Animo Repository, 2022)
This insider action research improved the onboarding program of an IT Consulting Development Team. As millions of individuals start a new job every year, organizations need to prepare new employees to perform their roles quickly and smoothly. A strategic onboarding program improves an organization’s competitive advantage since it facilitates the success of new employees. There are core components in employee onboarding that organizations should integrate into their process. By incorporating socialization and connection in employee onboarding, organizations facilitate new hires in creating vital interpersonal relationships and support mechanisms. Through Action Research, Methods of Inquiry, Systems Analysis, and Force Field Analysis, the action researchers decided to address the issue of inadequate project onboarding. Lewin’s Change Management Model, Four C’s of Onboarding, and Agile Methodology were utilized as third-person frameworks to guide the researchers throughout the action research process. In Cycle 1, the team established a structured project onboarding framework, onboarding checklist, and buddy system guide to address the lack of a project onboarding process, feedback mechanism, and socialization. After successful evaluation, the group continued to Cycle 2, wherein actual project onboarding was implemented to validate the output of the first cycle. In a broader context, this action research could be used as a reference for improving onboarding programs by implementing a structured onboarding process and focusing on socialization. The action researchers suggested employing feedback mechanisms and tools to measure the effectiveness of the onboarding.